Minderung der Erwerbsfähigkeit bei der Berufskrankheit 5103: Trends und Vergleich der Begutachtungspraxis von 2010 – 2015 - Hiller, Julia; Braun, Michael; Drexler, Hans (Dermatologie in Beruf und Umwelt, 2016)
Introduction: New recommendations for the assessment of the loss of earning capacity (LEC) were compiled after "squamous cell carcinoma and multiple actinic keratoses of the skin through natural UV radiation" and introduced as an occupational disease (BK 5103) in Germany in January 2015. The practice of medical reporting and principles for the estimation of LEC were analyzed. Methods: 108 consecutive medical expert reports from 2010 until July 2015 were identified and the LEC as well as further data were recorded. Additionally the data were used to determine and compare the LEC according to the two available assessment charts. Results: Recognition as an occupational disease was recommended for 59,2% of the collective and the LEC was predominantly (> 80%) rated with less than 20%. A comparison between the LEC values determined by the two varying LEC charts showed a slightly higher average value under the old chart (8,4% vs. 6,9%), which was also applicable to more cases and therefore included more cases with precanceroses (63% vs. 56%). In a direct comparison of the two charts higher differences of 10-20% in the determined LEC appeared especially among cases with squamous cell carcinoma. This was caused by a modification of the assigned LEC rates and standards for the disease activity between the two charts. Conclusions: A revision of the recommendations for the LEC was necessary after the introduction of a new occupational disease. By this, consistent standards for the evaluation of disease cases are provided and more fairness among different occupational diseases can be reached.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Actinic keratosis; Loss in earning capacity; Occupational disease; Squamous cell carcinoma